Development of an IoT-Based Solar Power Plant (PLTS) Experimental Kit as a CPS–STEM Learning Media in Junior High School - Putra, Gede Mudita Edi; Sriyanti, Ida; Marlina, Leni (Universitas Islam Negeri Ar-Raniry, 2026)
Science learning in junior high schools is still dominated by abstract and teacher-centered approaches, failing to realize the principles of pedagogical Deep Learning, which emphasizes mindful, meaningful, and joyful student understanding. This study aimed to develop an Internet of Things (IoT)-based Solar Power Plant (PLTS) experiment kit as a valid, practical, and effective Creative Problem Solving–STEM learning media. The study employed a 4D development model (Define, Design, Develop, Disseminate) with a one-group pretest-posttest design. The developed product consisted of solar panels, a Solar Charge Controller, a battery, and an inverter, integrated with an ESP32-based IoT module, relays, sensors, and the Telegram Bot platform. Validation was conducted by five experts using the Content Validity Index (CVI). The research subjects were 104 ninth-grade students at SMP Negeri 02 Semendawai Timur. The results showed that the IoT-based PLTS experiment kit was highly valid (CVI = 0.90) and very practical, with an average learning implementation of 84.75% and a positive student response of 89.03%. Furthermore, the kit was effective in improving students' Creative Problem Solving abilities, achieving an N-gain value of 0.53 (moderate category). This IoT-based PLTS experiment kit provides a learning experience that aligns with the demands of Industrial Revolution 4.0 and the principles of holistic educational Deep Learning.